Avaliação da motilidade ocular pré e pós-operatória em pacientes submetidos à cirurgia para implante de drenagem para tratamento do glaucoma: análise de série de casos e revisão de literatura - Ronconi, Cristiana Soares [UNIFESP] (2016)
OBJECTIVE: To evaluate changes in ocular extrinsic motility and ocular positioning in the primary position of the gaze in the pre and postoperative period of patients submitted to the implantation of drainage devices for the treatment of glaucoma. METHODS: A prospective study was carried out to evaluate extrinsic ocular motility and ocular positioning in the primary position of the eyes of patients who underwent drainage implant surgery to treat glaucoma. Demographic data, previous ophthalmological history, presence of subjective complaints of diplopia in the pre and postoperative period, and investigation of heterotropies and heterophores before and after surgery were analyzed. RESULTS: Of the total of 14 patients studied, eight (57.14%) patients were orthotropic and six (42.85%) had a deviation before surgery. At the end of the follow-up, eight (57.14%) patients had ocular deviation, and four (28.57%) patients maintained the same range of preoperative deviation, two (14.28%) patients presented increased And two (14.28%) patients developed new deviations. The frequency of development / worsening of postoperative deviations was 28.57%. All the patients presented divergent deviation in the pre and postoperative period. The diagnosis of Neovascular glaucoma was a possible predisposing factor for the development of postoperative deviation, since three (75%) of the patients who presented development / worsening of the deviations were diagnosed (versus 33.33% of those who did not present a deviation ). CONCLUSIONS: The incidence of ocular deviations and changes in ocular motility in the postoperative period of patients submitted to the Baerveldt implant - 350 mm2 of this study is within the range presented by previous studies. Differently from most of the published studies, in which the preoperative examination was not performed, this study showed that half of the patients who had a postoperative deviation presented it before surgery. This reinforces the importance of the evaluation of extrinsic ocular motility in the preoperative examination, besides the need for orientation of the patients with indication of this surgery for the treatment of glaucoma regarding the possibility of this adverse effect.